Differentiating “Attachment Difficulties” From Autism Spectrum Disorders and Attention Deficit Hyperactivity Disorder: Qualitative Interviews With Experienced Health Care Professionals - Coughlan, Barry; van IJzendoorn, Marinus H.; Woolgar, Matt; Weisblatt, Emma J. L.; Duschinsky, Robbie (Frontiers in Psychology, 2022)
Objectives: Attachment difficulties is an umbrella term often used to describe various forms of non-secure attachment. Differentiating ‘attachment difficulties’ from autism spectrum disorder (hereafter autism) and attention deficit hyperactivity disorder (hereafter ADHD) has been characterised as challenging. Few studies have explored how this happens in practice, from the perspective of professionals. Design: Qualitative study. Method: We conducted in-depth semi-structured interviews with (n=17) healthcare professionals from five NHS Foundation Trusts in the United Kingdom. Participants were recruited using a combination of snowballing, convenience and purposive sampling. Data were analysed using a thematic approach. Results: We identified six interrelated themes that might reflect difficulties with differential conceptualisation. These include: a clinical lexicon of attachment; approaching attachment with caution; contextual factors; perceived characteristic behaviours; assessing attachment and adjacent supports; spotlighting intervention and dual conceptualisation. Conclusion: Our results indicate some of the ways suspicions around attachment are raised in practice. We advocate for more dialogue between research and practice communities on issues of differential conceptualisation. We call for collaboration between a panel of experts consisting of attachment and neurodevelopmental orientated practitioners and researchers, to clarify issues around differentiating between attachment difficulties, ASD and ADHD.